Novel synthesis of crystalline mesoporous tin dioxide doped with nanogold - Tariq Aqeel; Heather F. Greer; Ali Bumajdad (Kuwait Journal of Science)
We report the successful synthesis of a new material, a crystalline mesoporous tin dioxide (m-SnO2) framework that contains nanogold clusters (m-SnO2-Au), prepared using a direct soft method under ambient pressure. The structure, bulk, and surface properties of this new material are analyzed and confirmed by N2 adsorption–desorption analysis, powder X-ray diffraction (XRD), high resolution transmission electron microscopy (HRTEM), energy dispersive X-ray (EDX), X-ray photoelectron spectroscopy (XPS), and UV-Vis spectroscopy. The material possesses a high Brunauer–Emmett–Teller (BET) surface area of 97 m2g–1, a narrow pore size distribution (2.1 to 3.3 nm) with an average pore diameter of 2.7 nm, and an average pore volume of 0.06 cm3g–1. We believe that the nanogold clusters initially occupy the pores of the mesoporous tin dioxide, thus restricting their growth before diffusing into the walls of tin dioxide during the second heat treatment. The median nanogold cluster size is 1.4 nm, indicating that this method controls both the porous structure and the size of the cluster within. The synthesized m-SnO2-Au material has a relatively small bandgap of 3.0 eV, as determined using the Kubelka-Munk function. The UV-Vis and white-light optical sensitivities of m-SnO2-Au are considerably higher than those of the parent material m-SnO2.